Prevalence and risk factors associated with fasciolosis in the southern region of Masvingo province - Mashate, Kudzai (Midlands State University, 2019)
Fasciolosis is a zoonotic disease of economic importance caused fasciola species and intermediate host Lymnaeid natalensis. The research aims to bring awareness to the farmers on the economic effects of fasciolosis in the beef production as well as its economic effects to the public health .A study to investigate the prevalence of fasciolosis and its associated risk factors was carried out at Koala park abattoir in Chiredzi district Zimbabwe. A total of 20553 cattle were delivered at Koala Park for slaughter with the objective of finding out if there is an association between prevalence and animal breed, animal sex, season of measurement and area of origin. From the animals slaughtered between January 2016 and December 2017, 1584 cattle were detected positive with adult and immature fasciola species. The average prevalence was 7.7% (n=1584). This study proves that, there was an association between prevalence of bovine fasciolosis and animal sex, animal breed and area of origin with (p<0.05) while there is no association between seasons of measurement and prevalence of fasciolosis with (p>0.05). I recommendend that further research on disease prevalence should be intensified to facilitate its management and control. Further researches need to be done in the southern region of Masvingo province on the use of coprological examinations to compare prevalence of the disease with the post-mortem examinations in the abattoirs.